Maritime Learning Innovation Based on the 2013 Curriculum in Early Childhood Education - Nuryati, Nuryati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to develop a maritime curriculum design for Early Childhood Education that is relevant to the needs of the maritime community in the Banten region. The research methodology used is R&D with the ADDIE model. The steps of this development research include Analysis, Design, Development, Implementation, and Evaluation. The population was conducted in 3 schools, with a sample of 5 teachers from the school: 2 teachers, one teacher from BKB Kemas Dahlia, and one teacher from TKIT Mathla'ul Anwar Sadatani. Data collection techniques used in this study were observation, interviews, documentation, and questionnaires. The results of the study, based on the analysis stage, found that students had low reading interest and difficulty understanding maritime material, so the researcher designed a maritime learning model by integrating the 2013 curriculum. After the design was carried out, it was then developed in the form of a table containing the arrangement of themes, subthemes, and indicators that correspond to the maritime material integrated with the 2013 curriculum. The implementation stage was trialed in 3 PAUD institutions in the Banten region. In the final stage, namely evaluation, validation is carried out by several experts according to their fields, as well as by PAUD teachers.